Using wearables to screen motor performance deterioration because of cancer and chemotherapy-induced peripheral neuropathy (CIPN) in adults: toward an early diagnosis of CIPN - Zahiri, Mohsen; Chen, Kevin M.; Zhou, He; Nguyen, Hung; Workeneh, Biruh T.; Yellapragada, Sarvari V.; Sada, Yvonne H.; Schwenk, Michael; Najafi, Bijan (Journal of geriatric oncology, 2019)
Objective - An essential component for optimizing quality of life in adults with cancer is determining the degree to which therapy may negatively impact motor-performance, so that patients can maintain their quality of life and independence. This study examined whether instrumented gait and balance could determine the magnitude of deterioration in motor-performance from chemotherapy-induced peripheral neuropathy (CIPN). - Methods - We recruited 84 adults with cancer (age=71.1±9.7years old, BMI=26.8±6.2kg/m2, gender=56%female) and 57 age-matched non-cancer patients (age=69.5±9.8years old, BMI=27.1±6.0kg/m2, gender=79%female). Based on clinical screening, the group with cancer was classified into two groups: participants with CIPN (CIPN+) and without CIPN (CIPN-). Gait and balance were quantified using validated wearables. The Vibration Perception Threshold (VPT) test was used to stratify the CIPN+ group into mild (Mild-CIPN) and severe (Severe-CIPN) subgroups. - Results - All gait and balance parameters were deteriorated in the group with cancer compared to non-cancer group with the largest effects observed for stride-time (11%, Cohen's effect size d=1.00, p<0.001) and eyes-closed ankle sway (94%, d=0.49, p=0.001). The same trend was observed when the Severe-CIPN subgroup was compared to the Mild-CIPN. VPT correlates significantly with motor deterioration, with the largest correlation found in stride-time (Rho=0.37, p=0.007). Severe-CIPN subjects were significantly older and overall had more deterioration in the majority of motor-performance parameters after adjusting for age (p<0.050). - Conclusion - These results confirmed the negative impact of CIPN on motor-performance with the largest effects on ankle stability and stride-time. VPT is a predictor of motor deterioration and may be used to determine the severity of CIPN symptom.